2001
DOI: 10.1136/vr.149.4.105
|View full text |Cite
|
Sign up to set email alerts
|

Serological, colostral and milk responses of cows vaccinated with a single dose of a combined vaccine against rotavirus, coronavirus and Escherichia coli F5 (K99)

Abstract: Twenty-five Ayrshire/Friesian cows were vaccinated once with a new combined vaccine against rotavirus, coronavirus and Escherichia coli F5 (K99) or given a saline placebo 31 days before the first expected calving date. Blood samples were taken from the cows at intervals from vaccination until seven days after calving and from their calves up to 28 days after birth, and colostrum and milk samples were collected from the cows at intervals for 28 days after calving. There was a significant increase in the mean sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
6
37
0
2
Order By: Relevance
“…Specific amplification of genotypes G5, G6, G8, G10 and G11 and genotypes P [1], P[5]-P [7] and P [11] was performed. Of note, genotypes G5, G8, G11, P [1], P [6] and P [7] were not detected. G6P [5] strains did not reveal any major differences between strains from vaccinated and non-vaccinated herds ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific amplification of genotypes G5, G6, G8, G10 and G11 and genotypes P [1], P[5]-P [7] and P [11] was performed. Of note, genotypes G5, G8, G11, P [1], P [6] and P [7] were not detected. G6P [5] strains did not reveal any major differences between strains from vaccinated and non-vaccinated herds ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…This gives key information for the development of appropriate vaccines for cattle. The most effective rotavirus vaccination strategy in cattle consists of promoting increased and prolonged anti-rotavirus protective antibody titres in mammary secretions of vaccinated pregnant cows [5,6], thus conferring passive protection to newborn calves. Indeed, it has been demonstrated that when calves are fed with colostrum from vaccinated dams from the first hours of life until they develop their own immunity, anti-rotavirus specific antibodies present in colostrum reduce the incidence of diarrhoea caused by rotavirus and viral shedding by calves infected with rotavirus.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were shown in another study, where a combined vaccine against rotavirus, coronavirus and E. coli was used to immunise pregnant cows. In these studies high titres of specific antibodies were measured in the colostrum and milk of dams to three components of the applied vaccine (Crouch et al, 2001). Makoschey et al (2012) have shown the effect of colostral antibodies from cow's vaccinated pre-partum with Bovilis ® Bovipast RSP on the passive immunity of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most important protective role is played by specific antibodies against antigens present in the neonate's environment (Riedel-Caspari, 1993;Korhonen et al, 2000b;Le Rousic et al, 2000;Crouch et al, 2001;Pisarska et al, 2002). Maternal antibodies, obtained from the colostrum and milk, protect the neonate against infections until its own efficient specific immune protection is developed (figs.…”
Section: Immunity Of the Neonate's Gastrointestinal Tractmentioning
confidence: 99%